Standing on the parent's shoulder or in its shadow? Alliance partner overlap between employee spinouts and their parents - Gaonkar, Shweta; Moeen, Mahka (Strategic Management Journal, 2023)
Abstract Research Summary Employee spinouts, defined as startups founded by prior employees of an industry firm, play a critical role in firm creation and knowledge transfer. Their superior performance often arises from resources and knowledge accrued during employment in parent firms. An understudied question is whether prior employment in parent firms affects an employee spinout's alliance formation, given that alliances are critical to startups' survival and commercial success. This article examines when an employee spinout's alliance partners overlap with the parent's partners. Drawing on alliance formation patterns of U.S. medical device spinouts founded between 1990 and 2013, we find that spinouts building on their parents' technologies tend to have a greater partner overlap with their parents, whereas product market overlap leads to fewer overlapping partners. Managerial Summary A rich context for entrepreneurs to identify new opportunities is through their employment in existing industry firms. When employees leave their job and create a spinout, their employment experience often provides them superior knowledge and expertise. Our study of medical device startups uncovers another distinctive feature of employee spinouts, that is, access to their employer's alliance partners. However, for such opportunities to come to fruition, entrepreneurs need to pay attention to their technical and product market positioning relative to their past employers. When spinouts build on their employer's technologies without challenging them in the product space, they can leverage connections to their employer's partners. This alliance strategy may free spinouts from the alliance formation struggles faced by resource‐deficient startups.